Development of spirometer to solve the problem of respiratory system - ยาอินตา นิกร; โพธิสุข บุศรา; ประภัทรสิริ บุญญาดา; กวินกุล เมธัส; ยาอินตา วัชรวลี; โตวิชา วรรณชนก (Community and Social Development Journal, 2019)
This research aims to study the problems of health in the respiratory system, the make the Spirometer and to study the effect of using the Spirometer to problem solving of health in the respiratory system that is an experimental research. The populations used in the research have 2 groups, including elderly volunteers (aged over 60 years old) and volunteers under 60 years old in the area of Tha Klwang Municipality, Saraphi District, Chiang Mai Province. The populations used in collecting data are 50 samples. It was found that the elderly often find the problem of respiratory system, including the capacity of the lungs will decrease which is leading to Atelectasis to the elderly easily and it still found the diseases of respiratory system, namely Asthma, Tuberculosis, Chronic Obstructive Pulmonary Disease and Emphysema. Therefore, a way to be able to help the lungs expansion that is to exercise the lungs by means of wind suction that will make the body to get more oxygen and help to breathe more efficiently The production of an Incentive Spirometer NK1 is to develop for using as a tool to help the lungs expansion that is designed according to scientific principles and the effectiveness of the Incentive Spirometer by using the principle of replacing the wind with water in order to measure the volume of air that will go into the lungs. The result of using Spirometer in the Incentive Spirometer NK1 found that does not negatively affect to health of the tester in any way, but there is good result for those who have high blood pressure by having the trend of decreasing after the test of 77.27 percent, in the elderly can help increase the air volume to the lungs at good level (940 cc.), and at a very good level (1233 cc.) with normal group.